2021
DOI: 10.1001/jamanetworkopen.2021.35353
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sodium-Glucose Transport Protein 2 Inhibitor Use for Type 2 Diabetes and Incidence of Gout in Taiwan

Abstract: IMPORTANCEThe use of sodium-glucose transport protein 2 (SGLT2) inhibitors is currently a standard intervention in patients with type 2 diabetes (T2DM) and exerts favorable pleiotropic effects to consistently lower blood urate levels. However, to date, no association between SGLT2 inhibitor use and the incidence of gout have been established. OBJECTIVE To investigate whether prescribed SGLT2 inhibitors are associated with lower gout incidence in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Previous post hoc analyses of randomized clinical trials [23][24][25]27 showed that SGLT2i reduced serum urate level, incident hyperuricemia, and incident gout in patients with type 2 diabetes or chronic heart failure, compared with placebo. Several observational studies 22,26,28,29 also reported that initiation of SGLT2i treatment was associated with a lower risk of incident gout than initiation of DPP-4i or GLP-1 RA treatment in patients with type 2 diabetes. However, to our knowledge, no study has previously assessed whether SGLT2i reduces the risk of recurrent gout flares.…”
Section: Discussionmentioning
confidence: 99%
“…Previous post hoc analyses of randomized clinical trials [23][24][25]27 showed that SGLT2i reduced serum urate level, incident hyperuricemia, and incident gout in patients with type 2 diabetes or chronic heart failure, compared with placebo. Several observational studies 22,26,28,29 also reported that initiation of SGLT2i treatment was associated with a lower risk of incident gout than initiation of DPP-4i or GLP-1 RA treatment in patients with type 2 diabetes. However, to our knowledge, no study has previously assessed whether SGLT2i reduces the risk of recurrent gout flares.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in two population‐based new‐user cohort studies, SGLT2 inhibitor use was associated with significantly reduced risk of gout when compared to individuals with T2DM who were prescribed GLP‐1RAs 38,39 . Several studies have also observed significant anti‐gout benefits with SGLT2 inhibitors versus dipeptidyl peptidase (DPP)‐4 inhibitors in T2DM 39–41 . One unique feature seen with SGLT2 inhibitor therapy is an up to twofold increase in fasting ketone, that is, BHB levels, which have significant anti‐inflammatory effects via NLRP‐3 inflammasome inhibition, and antioxidant effects via SIRT1 activation 42 .…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Several studies have also observed significant anti-gout benefits with SGLT2 inhibitors versus dipeptidyl peptidase (DPP)-4 inhibitors in T2DM. [39][40][41] One unique feature seen with SGLT2 inhibitor therapy is an up to twofold increase in fasting ketone, that is, BHB levels, which have significant anti-inflammatory effects via NLRP-3 inflammasome inhibition, and antioxidant effects via SIRT1 activation. 42 Given the inverse relationship between SIRT1 and xanthine oxidase activity, SGLT2 inhibitors may also decrease xanthine oxidase activity by this SIRT1-mediated effect, thereby lowering the local generation of ROS and intracellular uric acid.…”
Section: Discussionmentioning
confidence: 99%
“…The use of SGLT2 inhibitors was associated with a lower risk of gout (HR, 0.89; 95% CI, 0.82-0.96) compared with DPP4 inhibitors, particularly for patients receiving dapagliflozin (HR, 0.86; 95% CI, 0.78-0.95). A sensitivity analysis performed with gout-related medication also showed a significantly lower risk for gout incidence of 15% with SGLT2 inhibitors (HR, 0.85; 95% CI, 0.74-0.97) 32 .…”
Section: Role Of Sglt2i In Hyperuricemia and Goutmentioning
confidence: 94%